Stannathianes as activated polythiols for the synthesis of functionalized macrocyclic polythiolactones - Delgado Espinosa, Zuly Yuliana (2017)
We synthesized novel macrocyclic dithiolactones bearing endocyclic ether, polyether and lactone groups using new stannadithianes as tin templates in the condensation reaction with acid dichlorides and demonstrated an extension of this method toward synthesizing spirotetrathiolactones of controlled size. The structures of all synthesized compounds were characterized by spectroscopic methods.